Recurrence of endometrioma following conservative ovarian endometrioma cystectomy: Laparoscopy versus laparotomy - Chamnan Tanprasertkul (2018)
© 2015, Medical Association of Thailand. All rights reserved. Objective: To investigate the recurrence rate and disease-free interval between laparoscopy versus laparotomy for the conservative surgery of endometrioma. Material and Method: A retrospective cohort study was conducted. The medical records of reproductive women who underwent conservative ovarian cystectomy surgery (laparoscopy or laparotomy) for endometrioma at Thammasat University Hospital were retrieved. The patients were followed through 24 months to evaluate the recurrence of endometrioma. Propensity scoring was used to adjust for confounding by indication and confounding by contraindication. Model for competing time to event was used in analysis. Results: One hundred and twenty-eight and 114 patients were enrolled in laparoscopy and laparotomy groups, respectively. Mean age and body weight in laparotomy group were statistically higher than those in the other group were. Mean height and body mass index were, however, not statistically different in either groups. In addition, the stage of disease and bilaterality in both groups were comparable. Diameter of endometrioma in laparotomy group was significantly larger than that in laparoscopy group (7.0±2.5 vs. 6.2±1.8 cm, respectively; p = 0.004). After adjusting for propensity scoring, the endometrioma recurrence rate was significantly higher in laparoscopy group as compared to laparotomy group (27.3% vs. 14.9%, respectively; p = 0.02). However, the cumulative rate of pregnancy after surgery was not statistically different (4.7% vs. 4.4%, respectively; p = 1.0). Conclusion: The present study has demonstrated that the surgical technique has a strong impact on the recurrence or disease-free interval. Laparoscopy might not eradicate the disease pathology as effectively as open laparotomy in some situations, such as in cases with complexity of disease.